Correlation between structural, optical and magnetic properties of Mn-doped ZnO - Kumar P.; Singh B.K.; Pal B.N.; Pandey P.C. (My University, 2025)
We have investigated the structural, optical and magnetic properties of Mn-doped ZnO nanoparticles with different doping concentrations (0, 2, 4 and 6 %) synthesised by sol–gel method. Lattice parameters, cell volume, atomic packing fraction, crystallite size and confirmation of hexagonal wurtzite crystal structure have been studied by X-ray diffraction data. Surface morphology as well as grain size and the presence of all the elements have been confirmed by scanning electron microscope and energy-dispersive X-ray spectroscopy, respectively. The decrease in lattice parameters ratio (c/a) with Mn concentration indicates lattice distortion with the incorporation of Mn2+ ions at Zn2+ site of ZnO structure, which has been confirmed by Raman analysis. It has been observed that microstructure defects induced some extra Raman vibration modes. Ultraviolet–visible analysis shows that absorption edge lies in visible region, and encroachment in visible region increases, while energy band gap decreases with the increase in Mn concentrations. We have recorded FTIR spectra at room temperature to study the vibrational bands present in Zn1−xMnxO samples. The magnetic study of samples indicates ferromagnetic behaviour at room temperature. The magnetic properties increases with doping concentration due to small lattice distortion and defects. © 2016, Springer-Verlag Berlin Heidelberg.